Accumulation and Primary Metabolism of Nitrate in Lettuce (Lactuca Sativa L. Var. Youmaicai) Grown Under Three Different Light Sources. Issue 17 (24th September 2016) - Liu, Hui; Fu, Yuming; Yu, Juan; Liu, Hong
ABSTRACT: Light-emitting diodes (LEDs) hold great potential as electric light source for leafy vegetable production in controlled environment. However, most of LED lights in vegetable cultivation were only combined with red and blue LEDs, and the spectral composition was oversample. Previous studies reported that light spectral composition could influence nutritional quality of vegetables, e.g., nitrate content. In order to better understand the influence of spectral composition on nitrate accumulation of leafy vegetables grown in closed-type system. The nitrate content, nitrate primary metabolism of 35-day-old lettuce (Lactuca sativa L. Var. youmaicai) in vivo and its biomass were investigated. The results showed that cool white fluorescent light (T5) and high-pressure sodium light (HPS) with wide spectrum significantly reduced nitrate content in lettuce than red and blue combination LED light (RB-LED) treatment. Our findings demonstrated that a proper optimizing procedure of light spectrum with supplemental other wavebands in RB-LEDs is necessary for reducing nitrate accumulation of lettuce.